Correction: Correction: AKT Inhibitors Promote Cell Death in Cervical Cancer through Disruption of mTOR Signaling and Glucose Uptake. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0107846.].